Kurikulum 2013 dan Kurikulum Cinta Kemenag: Strategi Integratif dalam Pendidikan Karakter dan Spiritual: Strategi Integratif dalam Pendidikan Karakter dan Spiritual - Syaripudin, Ahmad; Sukiman; Hasna, Raudhatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the potential integration of the Love Curriculum in Islamic primary education at Madrasah Ibtidaiyah, particularly in efforts to shape students with noble character, spirituality, and environmental awareness. The background of this research relates to the challenges of globalization that influence the character and spirituality of students in Indonesia, as well as the importance of strengthening the affective and spiritual dimensions in education. Although the 2013 Curriculum has accommodated character education, the implementation of noble values is often overshadowed by a focus on academic achievement. This research uses a mixed methods approach, combining qualitative and quantitative methods to gain an in-depth understanding of teachers' readiness, understanding, and enthusiasm regarding the implementation of the Love Curriculum. The findings show that 92% of teachers agree on the importance of a love-based curriculum, although only 41% fully understand the concept. Although the Love Curriculum has not been officially implemented, values such as love for God, others, the environment, and the homeland have begun to be implicitly taught in learning. However, significant challenges remain, including the lack of official modules and training for educators, which limits the integration of these values. This study concludes that the Love Curriculum has the potential to become a transformative curriculum innovation, provided there is sufficient structural, pedagogical, and regulatory support. It is hoped that Madrasah Ibtidaiyah can become a pioneer in the implementation of this curriculum as a step toward holistic, character-based, and ecologically aware education.